External morphology of immatures during the post-embryonic development of Mischocytarus nomurae Richards (Hymenoptera: Vespidae) - Rocha, A. A.; Giannotti, E. [UNESP] (Universidade Estadual de Feira de Santana, 2016)
We describe here the immatures of Mischocytarus nomurae Richards from twenty colonies collected in the municipality of Rio de Contas in the Chapada Diamantna, Bahia State, Brazil. We determined the number of larval instars in post-embryonic development and measured 145 eggs, 353 larvae, 12 prepupae, and 59 pupae. Egg lengths varied from 0.80 to 1.33 mm and their widths from 0.33 to 0.50 mm. The average rate of growth of the larvae was 1.48. Cephalic capsule widths varied from 0.20-0.43 mm in the 1st instar larvae, from 0.47-0.63 mm in the 2nd instar, 0.67-0.83 mm in the 3rd instar, 0.87-1.20 mm in the 4th instar, and 1.37-1.73 mm in the 5th instar larvae. The cephalic capsule of the 1st instar larva was smaller than the width of the egg. The median widths of the 5th instar larvae and the pre-pupae cephalic capsules did not differ significantly. The species has two abdominal lobes that are highly projected forward, and the diameter of first thoracic spiracle is 3.1 tmes greater than the second. M. nomurae shows development paterns typical of the genus.
Keywords: Abdominal lobe; Larvae; Polistnae; Social wasps; Spiracles